The Shimmering Is All There Is : On Nature, God, Science, and More - Kohout, Heather Catto, 1959-2014 (Book collections on Project MUSE., 2021)
"The Shimmering Is All There Is: On Nature, God, Science, and More is a collection of essays and poems by the late Heather Catto Kohout. A native of San Antonio, Heather was a disciplined and original thinker and writer. Her education, experience, and temperament-as a loving wife, mother, and daughter; a proud Texan; a teacher and scholar with graduate degrees in English literature and religion; and the founder of a residency program for environmental writers and artists at a ranch in the Texas Hill Country-permeate every word she wrote. She had a unique combination of empathetic imagination, profound spirituality, cosmic sensibility, and an ability to laugh-gently-at her fellow creatures and, especially, herself. Heather Kohout's essays and poems are thoughtful, profound, and generous, shifting constantly between the specific and the universal and carrying throughout a message of stewardship. She was an environmentalist at heart, but her writing explores so much more: nature, art, theology, science, food, and family. She wrote about Mexican teenagers who dress as angels in an attempt to halt drug-related violence; the perils of industrial agriculture; the pleasure of letting the chickens out of their coop in the morning; and the battle to save the Georgetown salamander. Always, she wrote about what it means to try to live an ethical life and to be fully human as a part of, not in opposition to, nature. These essays and poems exemplify the best of Texas womanhood: stubborn independence, fierce conviction, good humor, and instinctive generosity and kindness"--